Role of Bioactive Constituents of Panax notoginseng in the Modulation of Tumorigenesis: A Potential Review for the Treatment of Cancer - Tan, Ming-Ming; Chen, Min-Hua; Han, Fang; Wang, Jun-Wei; Tu, Yue-Xing (Frontiers in Pharmacology, 2021)
Cancer is a leading cause of death, affecting people in both developed and developing countries. It is a challenging disease due to its complicated pathophysiological mechanism. Many anti-cancer drugs are used to treat cancer and reduce mortality rates, but their toxicity limits their administration. Drugs made from natural products, which act as multi-targeted therapy, have the ability to target critical signaling proteins in different pathways. Natural compounds possess pharmacological activities such as anti-cancer activity, low toxicity, and minimum side effects. Panax notoginseng is a medicinal plant whose extracts and phytochemicals are used to treat cancer, cardiovascular disorders, blood stasis, easing inflammation, edema, and pain. P. notoginseng’s secondary metabolites target cancer’s dysregulated pathways, causing cancer cell death. In this review, we focused on several ginsenosides extracted from P. notoginseng that have been evaluated against various cancer cell lines, with the aim of cancer treatment. Furthermore, an in vivo investigation of these ginsenosides should be conducted to gain insight into the dysregulation of several pathways, followed by clinical trials for the potential and effective treatment of cancer.